Facing an uncertain future: how forest and people can adapt to climate change - Locatelli, Bruno; Kanninen, M.; Brockhaus, Maria; Colfer, C.J.P.; Murdiyarso, Daniel; Santoso, H. (Center for International Forestry Research, 2008)
The most prominent international responses to climate change focus on mitigation (reducing the accumulation of greenhouse gases) rather than adaptation (reducing the vulnerability of society and ecosystems). However, with climate change now inevitable, adaptation is gaining importance in the policy arena, and is an integral part of ongoing negotiations towards an international framework. This report presents the case for adaptation for tropical forests (reducing the impacts of climate change on forests and their ecosystem services) and tropical forests for adaptation (using forests to help local people and society in general to adapt to inevitable changes). Policies in the forest, climate change and other sectors need to address these issues and be integrated with each other—such a cross-sectoral approach is essential if the benefits derived in one area are not to be lost or counteracted in another. Moreover, the institutions involved in policy development and implementation need themselves to be flexible and able to learn in the context of dynamic human and environmental systems. And all this needs to be done at all levels from the local community to the national government and international institutions. The report includes an appendix covering climate scenarios, concepts, and international policies and funds.